Effect of the shell material and confinement type on the conversion efficiency of core/shell quantum dot nanocrystal solar cells. (20th April 2018) - Sahin, Mehmet
Abstract: In this study, the effects of the shell material and confinement type on the conversion efficiency of core/shell quantum dot nanocrystal (QDNC) solar cells have been investigated in detail. For this purpose, the conventional, i.e. original, detailed balance model, developed by Shockley and Queisser to calculate an upper limit for the conversion efficiency of silicon p–n junction solar cells, is modified in a simple and effective way to calculate the conversion efficiency of core/shell QDNC solar cells. Since the existing model relies on the gap energy ( ) of the solar cell, it does not make an estimation about the effect of QDNC materials on the efficiency of the solar cells, and gives the same efficiency values for several QDNC solar cells with the same . The proposed modification, however, estimates a conversion efficiency in relation to the material properties and also the confinement type of the QDNCs. The results of the modified model show that, in contrast to the original one, the conversion efficiencies of different QDNC solar cells, even if they have the same, become different depending upon the confinement type and shell material of the core/shell QDNCs, and this is crucial in the design and fabrication of the new generation solar cells to predict the confinement type and also appropriate QDNC materials for better efficiency.